INCOME OVER FEED COST DAN R-C RATIO USAHA TERNAK SAPI MELALUI PEMANFAATAN LIMBAH KELAPA SAWIT - Zakiatulyaqin Zakiatulyaqin; I. Suswanto; R.B. Lestari; D. Setiawan; A.M.S. Munir (JURNAL ILMIAH PETERNAKAN TERPADU, 2017)
Based  on  the  palm oil plantation growth,  Indonesia  has  very  high  potential  to  increase  by product of palm oil  through  the implementation of adapted and liable technology. The  research was conducted to study the ability of by product of palm oil meal addition concentrates on the economic performance of cattle. This experiment used a randomized block design, with 3 treatments and 3 blocks. Treatments consisted of P1 14% crude protein (palm frond and by product of palm oil concentrate), P2 16% crude protein (palm frond and by product of palm oil concentrate), and P3 18% crude protein (palm frond and by product of palm oil concentrate). The experiment was conducted for 4 months with the adaptation periods for 2 weeks. Parameters measured were income over feed cost (IOFC) and revenue cost ratio. The results showed that the by product of palm oil meal addition on different concentrate did not significantly (P>0,05) affect IOFC  and revenue cost Ratio. It is concluded that based on the IOFC and revenue cost ratio, by product of palm oil concentrate can be combined with P1,  P2  and P3 concentrate.  Keywords: Feed, Income Over Feed Cost (IOFC), R-C ratio